The fear of missing out influence on excitement-seeking and the thrill of a sale - Stephen Bok; James Shum; Maria Lee (Cogent Business & Management)
Fear of missing out (FOMO), conceptualized from self-determination theory (SDT), is a sense of disconnect from others that produces negative emotions (e.g., anxiety). Social Cognitive Theory of Internet Uses and Gratifications (U&G) explains the development of social media (SM) socio-structural value systems have created a feedback loop to share content for rewards. We investigate how consumers transfer FOMO to their purchasing behaviors to relieve negative emotions. Moderated meditation path analysis results (N = 873) displayed a direct positive relationship between FOMO with excitement-seeking and deal-seeking. The need for online social feedback (NFOSF) positively mediated these main effects. Connection to community/group, as a moderator, heighted the NFOSF. Results evinced greater connection to a community has a feedback loop to seek and share exciting content. Excitement can also come from the thrill of buying a product on sale.